THE MORPHOSYNTAX OF TENSE IN NORTHERN KURDISH - ALI , BAYAN JUMAA; SULAIMAN, MOHAMAD SALIH A. (Journal of Duhok University, 2023)
The relationship between morphology and syntax has become an important aspect of the structural description of a language. Some syntax and morphology facts are thought to partially overlap, implying that they are important as morphosyntactic phenomena and morphological in verb forms are grammatically significant and can point to various syntactic categories, such as tense, aspect, agreement, voice, mood, negation and causality. In the linguistic literature on NK, this topic has not gotten much consideration. From this perspective, the present study investigates the morphosyntactic features of the tense in Northern Kurdish (henceforth NK). It aims to provide a systematic descriptive account of the morphemes involved in the realization of the syntactic category of tense in NK, the number and types of those morphemes as well as their order in relation to the verb stem. The data for this qualitative study are gathered from grammar textbooks, literary materials, proverbs, and everyday interactions. The qualitative analysis of the data revealed that NK verb forms occasionally display a bit complexity; the lexical root can bear, in addition to the tense inflections, markers for agreement, voice, mood, negation, and causativity. Also, NK contains a rich system of person and number inflections, and the verb is marked for person and number in all tenses. Furthermore, mood in NK, communicated morphologically through prefixation, is closely associated with the realization of tense contrasts. It is hoped that the current study will fill a gap in this specific area of the morphosyntax of NK. And broaden current knowledge of this topic. The findings of the study will hopefully be of benefit to Kurdish language learners of EFL and translators